The Formulation of Classification for Islamization in Medicine: Review on 15 Years of Publications from Kulliyyah of Medicine - Shahar, MA; Idris, MF; Mohamad, CAC; Razali, ZA (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus